Sustainable urban development in Malmö. A city ready for tomorrow. - Radu-Costin, Ismănescu (Forum Landschaftsplanung - AbsolventInnenverband, 2021)
Urban planning is a major tool in determining the quality of life of people in any type of settlement. Attempts to create more sustainable neighborhoods or cities have materialized more and more often in all corners of the world. The trend to use sustainable materials and renewable energy has become widespread over the past few decades. In order to clarify as many aspects related to this topic as possible, I chose to analyze and present two specific cases of sustainable planning that have been put into practice in Malmö, Sweden. The article presents details of two projects: the newly built housing area „Bo01“ and the upgraded neighborhood „Ekostaden Augustenborg“, both located in Malmö, Sweden. The text highlights the importance of participatory planning, creation of urban green spaces that fit into the local network of green spaces, the creation of a master plan that includes long-term development measures that provide appropriate responses to the needs of citizens.
Keywords: Nachhaltige Stadtentwicklung; Ökologisches Bauen; Neubausiedlung; Quartiererneuerung; Energetische Sanierung; Bewohnerbeteiligung; Grünraumplanung; Projektbeschreibung